Computer Mediated Social Comparative Feedback Does Not Affect Metacognitive Regulation of Memory Reports - Rechdan, Joanne; Sauer, James D.; Hope, Lorraine; Sauerland, Melanie; Ost, James; Merckelbach, Harald (Frontiers in Psychology, 2017)
In two experiments, we investigated how social comparative feedback affects the metacognitive regulation of eyewitness memory reports. In Experiment 1, 87 participants received negative, positive, or no feedback about a co-witness’s performance concerning cued recall of a crime video. Participants then completed the task individually. There were no significant differences between negative and positive feedback groups on any measure. However, participants in both of these conditions volunteered more fine-grain details than participants in the control condition. In Experiment 2, 90 participants answered questions about a crime video. Experimental group participants received either positive or negative feedback, which compared their performance to that of others. Participants then completed a subsequent recall task, for which they were told their performance would not be scored. Feedback did not significantly affect participants’ confidence, accuracy, or the level of detail they reported in comparison to a no feedback control group. These findings advance our understanding of the boundary conditions for social feedback effects on meta-memory.